Association of reallocating time between physical activity and sedentary behavior on the risk of depression: a systematic review and meta-analysis - Wang, Yue; Sun, Jun; Zhang, Yuheng; Wang, Jiali; Lu, Songtao (Frontiers in Psychology, 2025)
Background and aimsSedentary behavior (SB) is a prevalent lifestyle factor and a risk factor for various health conditions, including depression (encompassing both clinically diagnosed depressive disorders and depressive symptoms). This study aimed to summarize the estimated impact of reallocating time spent in SB to light-intensity physical activity (LPA) or moderate-to-vigorous physical activity (MVPA) on the risk of depression from observational studies, as well as the impact of reallocating time spent in MVPA and LPA to SB.MethodsFour databases [PubMed, Scopus, SPORTdiscus, and PsycINFO (via EBSCOhost platform)] were searched and analyzed for relevant studies published up to August 2024. Meta-analyses were performed on the estimated regression coefficients (b) and 95% confidence intervals (CIs) for depression symptom scores. All statistical analyses were performed using STATA 16.0.ResultsTwenty-seven studies involving 702,755 participants met the inclusion criteria. Reallocating SB to LPA and MVPA was significantly associated with reductions in depression risk (b = −0.04, 95% CI = −0.06 to −0.03, p < 0.001; b = −0.11, 95% CI = −0.19 to −0.03, p = 0.004). Subgroup analyses indicated that reallocating 30 and 60 min of SB to LPA or MVPA was significantly associated with reduced depression risk, with significant differences in PA intensity and age, but not for 10 and 15 min groups. Conversely, reallocating LPA and MVPA to SB was significantly associated with increased depression risk (b = 0.11, 95% CI = 0.01 to 0.21, p = 0.039; b = 0.17, 95% CI = 0.08 to 0.25, p < 0.001). Subgroup analyses indicated that reallocating 30 min of LPA or MVPA to SB was significantly associated with increased depression risk, with no difference in PA intensity.ConclusionsReallocating SB to PA was beneficial, whereas reallocating PA to SB was detrimental to the risk of depression. The results highlight the importance of considering PA intensity and duration in the development of behavioral guidelines aimed at reducing the risk of depression.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=546666, identifier: CRD42024546666.